IMPLEMTASI KEBIJAKAN PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) DI BADAN PELAYANAN PERIZINAN TERPADU KOTA MANADO - Takumansang, Chintya Mellysa (ACTA DIURNA KOMUNIKASI, 2013)
The implementation policy towards the service for finding building permit in the office of integrated permitting service of Manado city can not be indicated as effective since there are aspects not yet optimal as its resources such as laborers, tools and facility still not enough. The implementation policy towards the service for finding building permit form the aspect of retribution target is optimal where as the certainty and quaranty of service cost from the aspect of time for finishing service is not yet suitable and correct. Keyword : Implementation Policy, Service Permit, Finding Building